2021
DOI: 10.1002/anie.202103087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Carbon Dioxide Hydrogenation over Pd/ZnO‐Based Catalysts: The Role of Palladium–Zinc Alloy in Selective Methanol Synthesis

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…This corresponds to a complete reduction of the palladium present, along with some of the zinc oxide, to yield a highly dispersed palladium-zinc alloy phase (RPd−Zn = 2.59 Å, RPd−Pd = 2.95 Å). [22] Exposure to the reaction mixture, and then carbon dioxide, does not affect the palladium-zinc alloy (Figure 2d). Overall, the fitting of k 3 -weighted Pd K-edge EXAFS of 2Pd-ZnO-np (RPd−Zn = 2.59 Å, RPd−Pd = 2.92 Å) shows that, once reduced in hydrogen, the nanoparticulate palladium-zinc phase is retained under all of the conditions applied, irrespective of the gaseous environment experienced (Tables 1 and S3).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 3 more Smart Citations
“…This corresponds to a complete reduction of the palladium present, along with some of the zinc oxide, to yield a highly dispersed palladium-zinc alloy phase (RPd−Zn = 2.59 Å, RPd−Pd = 2.95 Å). [22] Exposure to the reaction mixture, and then carbon dioxide, does not affect the palladium-zinc alloy (Figure 2d). Overall, the fitting of k 3 -weighted Pd K-edge EXAFS of 2Pd-ZnO-np (RPd−Zn = 2.59 Å, RPd−Pd = 2.92 Å) shows that, once reduced in hydrogen, the nanoparticulate palladium-zinc phase is retained under all of the conditions applied, irrespective of the gaseous environment experienced (Tables 1 and S3).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…According to EXAFS analysis (Figure 2d, Table S3), XRD (Figure 2e and Figures S5-S6), and TEM (Figures S7-S8), the resulting phase is a palladium-zinc alloy, in a good agreement with previous studies, where the formation of this phase was observed even at ambient pressure. [17,22,32] The formation of the palladium-zinc alloy phase is facilitated by hydrogen spillover and accumulation of hydrogen inside metallic palladium. [22] Furthermore, and irrespective of the difference in palladium particle size and distribution, the 2Pd-ZnO-i sample shows very similar behavior during operando XAS study (Figure S3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In Pd-Zn alloys, the SMSI effect between metallic Pd and ZnO at high temperatures ensures the formation of a stable alloy, although the nature of the active sites is the subject of scientific debate [77]. On the one hand, the formation of PdZn alloys often correlates with catalytic activity and methanol selectivity, [78][79][80][81] however, Pd decorated with ZnO x islands are partly discussed as active sites [82].…”
Section: Alloy Catalystsmentioning
confidence: 99%